Factors Influencing Technology Use in Aural Skills Lessons - Pomerleau Turcotte, Justine; Moreno Sala, Maria; Dubé, Francis (Revue musicale OICRM)

(untitled) (Observatoire interdisciplinaire de création et recherche en musique (OICRM), 2017)
In North America, aural skills (as) are usually taught to children during the instrumental music lessons. While learning musical dictation and sight-singing can be difficult for some learners, the use of appropriate technological tools could facilitate the process. However, the use of information and communication technologies (ict) by music teachers in aural skills instruction to children have not been documented. An online survey was conducted in the Province of Quebec (Canada) in order to answer the following questions: 1) To what extent do instrumental music teachers use ict when teaching as to children between 6 and 12 years old?; 2) Are the teachers’ socio-demographic characteristics, as training and perception of as teaching linked to the use and the frequency of use of ict? The results show that the use of ict to teach as is still relatively uncommon. Furthermore, it would be negatively correlated with age, competence felt during training and perceived competence to teach as. Finally, it appears that a smaller proportion of piano teachers and women use ict, or use them less often. A better understanding of the teachers’ perception of technology could help develop more adapted resources.